Obraza muzyki i poezji. O twórczości Stanisława Staszewskiego = Music and poetry contempt. On Stanisław Staszewski's output - Kubiak, Maciej (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The aim of the article is to present the works by Stanisław Staszewski which, despite being present in Polish popular culture for years, have not been thoroughly analysed in terms of their both textual and musical contents.
Keywords: Staszewski, Stanisław (1925-1973); piosenka - tekst; estetyka; gradacja; oddziaływanie; lyrics; aestetics; gradation; impact